2004
DOI: 10.1590/s0103-84782004000100006
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa do potencial de rendimento por estrato do dossel da soja, em diferentes arranjos de plantas

Abstract: O potencial de rendimento da soja pode ser modificado pelo arranjo de plantas. Esta alteração pode resultar da contribuição diferenciada dos estratos do dossel para a determinação do potencial. O experimento foi conduzido na Estação Experimental Agronômica da UFRGS, em Eldorado do Sul, RS, na estação de crescimento 2000/01, objetivando avaliar o potencial de rendimento em três estratos do dossel da soja em função da modificação do arranjo de plantas, em dois regimes hídricos. Utilizou-se a cultivar ‘BRS 137’, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 4 publications
1
15
0
18
Order By: Relevance
“…However, in the 2014/2015 growing season, an increase in plant density linearly reduced the number of grains per pod, both in the stem and branches (Table 2). Rambo et al (2004) also observed a linear reduction in this variable as a result of increase in soybean plant density. In this context, the reduction of resources availability for each plant may limit the grain filling, resulting in fewer grains per pod.…”
Section: Cv(%)mentioning
confidence: 68%
See 1 more Smart Citation
“…However, in the 2014/2015 growing season, an increase in plant density linearly reduced the number of grains per pod, both in the stem and branches (Table 2). Rambo et al (2004) also observed a linear reduction in this variable as a result of increase in soybean plant density. In this context, the reduction of resources availability for each plant may limit the grain filling, resulting in fewer grains per pod.…”
Section: Cv(%)mentioning
confidence: 68%
“…The maintenance of yield, despite the widely varying densities (105 to 430 thousand plants•ha -1 ), is likely a consequence of the high phenotypic plasticity of the soybean crop, as reported by several authors (Board 2000;Procópio et al 2013;Rambo et al 2004;Tourino et al 2002). According to Peixoto et al (2000), a reduction in the number of soybean plants per area is generally offset by an increment in the number of pods per plant.…”
Section: Resultsmentioning
confidence: 87%
“…Esse fato é agravado ao se considerar a contribuição do dossel inferior na produção de vagens e produtividade, que pode representar 35 a 45% do total produzido em uma planta de soja (Rambo et al 2004;Bahry et al 2014). Adicionalmente, a baixa qualidade na distribuição da RFA ao longo do dossel com o aumento da densidade de plantas também foi comprovada pela redução da TAL, da TCC e principalmente pela redução do k.…”
Section: Resultsunclassified
“…Nesse sentido, o ICG confirmou a mesma tendência para produtividade e peso de 1,000 grãos (Figura 7b), sendo que o máximo acúmulo de fi tomassa seca proporcionada por maiores densidades não resultou em máxima produtividade e peso de grãos, corroborando outros estudos (Rambo et al 2004;Procópio et al 2013 . Assim como em outros estudos (Procópio et al 2013;Silva et al 2013;Balbinot Junior et al 2015), o aumento da densidade de plantas não resultou em aumento de produtividade.…”
Section: Resultsunclassified
“…rate does not affect seed weight, since this characteristic is influenced in a greater degree by genotype compared with environmental conditions (Rambo et al, 2004). Balbinot Júnior et al (2015), working with row spacing, densities and seeding system for the cultivar BRS 294 RR, state that the number of seeds per pod and thousand-grain weight from the stems and branches were not affected by the treatments.…”
Section: Sources Of Variationmentioning
confidence: 99%